PENGARUH PENAMBAHAN CAMPURAN NITROBACTER SP DAN LACTOBACILLUS FERMENTUM TERENKAPSULASI TERHADAP KONSUMSI PAKAN, PERTAMBAHAN BOBOT BADAN, DAN KONVERSI PAKAN PADA KELINCI: Effect of Additional Nitrobacter sp and Lactobacillus fermentum Encapsulated on Feed Consumption, Weight Gain, and Feed Conversion Ratio of Rabbits - M Nurkholis; umi kalsum; Oktavia Rahayu Puspitarini (Departemen Nutrisi dan Makanan Ternak, Fakultas Peternakan, Universitas Hasanuddin, 2021)
Probiotics are feed additives (supplements) that contain nonpathogenic microorganisms that involve actively in the digestive system to increase productivity and health of the livestock. Nitrobacter Sp is nitrifying bacteria, they can convert nitrites into nitrates. The addition of Lactobacillus fermentum and Nitrobacter Sp encapsulation in feed is expected to be able to increase digestibility, inhibit pathogenic bacteria, neutralize ammonia, thereby increasing feed consumption, increasing body weight gain (BWG), and reducing the value of Feed Conversion Ratio (FCR). The purpose of this study was to analyze the additional Nitrobacter Sp and Lactobacillus fermentum encapsulated on feed consumption, BWG, and FCR of growing male rex rabbits. This study used a Randomized Group Design based on body weight with four treatments and four groups, each unit consisted of 2 rabbits, so a total of 32 rabbits have experimented in this study. The treatments are P0= feed without additional probiotics, P1= feed + 1,5 grams of probiotics/kg of feed, P2= feed + 3 grams of probiotics/kg of feed, P3= feed+ 4,5 gram of probiotics/kg of feed. The analysis of variance results showed that the treatments have a significantly effect (P<0,01) on feed consumption, BWG, and significant effect (P<0,05) on Lactobacillus fermentum and Nitrobacter probiotics can increase feed consumption, increase weight gain, and lower the FCR. The best result of additional Lactobacillus fermentum and Nitrobacter is 4,5 grams probiotics/kg feed with an average of 2159,13 grams/head of feed consumption, 354,88 grams/head of weight gain, and 6,12 of FCR. Keywordsi : Nitrobacter, Lactobacillus fermentum, Encapsulation, Productivity.